The ABC management of the acetabular fracture patient. Issue 2 (April 2022) - Balendra, Ganesh; Bassett, James William; Acharya, Mehool
Abstract: Acetabular fractures represent one of the most complex fractures treated by orthopaedic surgeons. Our understanding of these injuries is due to the seminal work of Robert Judet and Emile Letournel, whose classification system is still in use today. Letournel demonstrated that by achieving perfect anatomic reduction, excellent outcomes could be obtained in this challenging patient cohort. This review is a summary of our understanding of acetabular fracture patterns and their management and explores the various factors affecting clinical outcomes after surgical fixation of acetabular fractures.